Haemocholecyst related to gallbladder malignancy. (July 2020) - Ray, Sukanta; Ghosh, Ranajoy; Khamrui, Sujan; Kumar Das, Amit; Saha, Suman; Kumar, Dilip
A haemocholecyst is a clot-filled gallbladder caused by bleeding into its lumen. It is a rare entity with fewer than 50 cases reported in the English literature. Preoperative diagnosis is often not possible even with good quality cross-sectional imaging. Here, we present a case of a gallbladder mass, whose nature was only made clear at operation, where a hugely enlarged gallbladder was found filled with blood clots. There was neither liver infiltration nor regional lymphadenopathy. The clinical status of the patient demanded simple cholecystectomy. Histopathological examination, however, revealed a gallbladder adenocarcinoma, infiltrating the perimuscular connective tissue. Thus, more radical surgery was performed eight weeks later. At the 21-month follow-up, the patient was found to be well.